Automated Detection of Compressed Air Leakage in Pneumatic Stations - Tič, Vito; Baligač, Andrej (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Effective detection of compressed air leaks is crucial for improving energy efficiency in pneumatic systems. In this paper, we present an automated leak detection approach for a pneumatic workstation using integrated pressure and flow sensors. The system monitors the baseline operating cycle and identifies anomalies such as excess air consumption or pressure drops that indicate leakage. A Beckhoff PLC with TwinCAT 3 was used to collect real-time data, and a parallel simulation model was developed in Automation Studio to validate the approach. Experimental results from both simulation and a physical pneumatic station demonstrate that flow-based measurements are far more sensitive to small leaks than pressure-based methods. Even a 1 mm diameter leak orifice produced a significant increase in airflow consumption with minimal detectable pressure change. The comparison between simulated and real-world leak scenarios confirms the viability of continuous sensor-based monitoring for early leak detection in pneumatic systems.